ANALYSIS OF THE APPLICATION OF ISLAMIC BUSINESS ETHICS (CASE STUDY OF LOPO MANDHELING COFFEE PANYABUNGAN MANDAILING NATAL) - Hasibuan, Zahra Syahfitri; Jannah, Nurul; Silalahi, Purnama Ramadani (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This research aims to examine how the Islamic business ethics present at Lopo Mandheling Coffee align with Islamic business ethics, in which the author conducts a study titled “Analysis of the Implementation of Islamic Business Ethics at Lopo Mandheling Coffee Panyabungan Mandailing Natal.” Methodology: The method used is a qualitative approach. At Lopo Mandheling Coffee, good Islamic business ethics have been implemented in accordance with the principles of unity, balance, free will, and responsibility. Results: It can be concluded that Lopo Mandheling Coffee has implemented Islamic business ethics as a competitive advantage. It is as if we have implemented the obligation of performing the five daily prayers, providing assistance and support to orphans as a form of social and environmental concern, as well as responsibility. Limitations : The author's suggestion is that Lopo Mandheling Coffee Panyabungan is expected to remain steadfast in applying the principles of Islamic business ethics, improve the quantity and quality of Human Resource management, and enhance the company's capital by seeking investors. Contribution : Islamic-based business ethics must be applied in today's highly competitive business environment. Keywords: Islamic Business Ethics; Application; Lopo Mandheling Coffee Panyabungan.